The effect of oral zinc supplementation on cervicovaginal lavage fluid zinc level. (May 2020) - Takacs, Peter; Damjanovich, Peter; Sipos, Attila Gergely; Kozma, Bence
Abstract: Objectives: To investigate the effect of oral zinc supplementation on cervicovaginal lavage fluid (CVL) zinc level in pre and postmenopausal women. Study design: A prospective interventional cohort study was carried out by the enrollment of twelve premenopausal and ten postmenopausal women without significant gynecological conditions. Women received daily oral supplementation with 30 mg of zinc for two weeks. Clinical and demographic variables were stored in a dedicated database. Vaginal Health Index was calculated, and vaginal cytology was obtained. CVL and serum samples were collected in a standardized fashion before and after completion of the oral supplementation. Zinc and copper levels were measured by inductively coupled plasma optical emission spectrometry. Paired t -test was used to compare the before and after treatment results. Results: Serum zinc levels increased significantly both in the pre and postmenopausal women (0.88 ± 0.17 vs. 1.06 ± 0.23, p < 0.01 and 0.83 ± 0.24 vs. 0.96 ± 0.33, p < 0.01) after two weeks of daily oral zinc supplementation. CVL zinc level was significantly higher in the premenopausal group compared to the postmenopausal group before and after supplementation (0.13 ± 0.05 vs. 0.06 ± 0.04, p < 0.01 and 0.10 ± 0.03 vs. 0.05 ± 0.01, p < 0.01). Zinc supplementation had no significant impact on the CVL zinc level in either group. Neither serum nor CVL copper levels were affected by the zinc supplementation. There was no significant correlation between serum and CVL zinc or copper levels. Conclusion: Daily oral supplementation with 30 mg of zinc had no significant impact on CVL zinc level despite a significant rise in serum zinc level.